The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.5380/avs.v10i2.4431
|View full text |Cite
|
Sign up to set email alerts
|

ISOLAMENTO DO Ureaplasma diversum EM MUCO VULVOVAGINAL DE VACAS LEITEIRAS REPETIDORAS DE ESTRO NO ESTADO DE ALAGOAS – BRASIL

Abstract: O Ureaplasma diversum é um patógeno oportunista do trato genital dos bovinos que causa surtos de vulvovaginite granular, seguidos de abortamento e redução da eficiência reprodutiva do rebanho. O presente estudo foi desenvolvido com o objetivo de avaliar a relação entre a extensão e a gravidade das lesões de vulvovaginite observadas com o isolamento de Ureaplasma diversum em amostras colhidas diretamente da mucosa vulvovaginal, em fêmeas de aptidão leiteira repetidoras de estro no estado de Alagoas, Brasil. A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
5
0
4
Order By: Relevance
“…Cardoso et al (1997) (Landford 1975, Ruhnke et al 1984, Trichard & Jacobz 1985. U. diversum já foi isolada de surtos de vulvovaginite granular, seguidos de abortamento e redução da eficiência reprodutiva (Nascimento et al 1998, Cardoso et al 2000a, 2006, Cardoso & Vasconcelos 2004, Nascimento et al 2005, Oliveira Filho et al 2005.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Cardoso et al (1997) (Landford 1975, Ruhnke et al 1984, Trichard & Jacobz 1985. U. diversum já foi isolada de surtos de vulvovaginite granular, seguidos de abortamento e redução da eficiência reprodutiva (Nascimento et al 1998, Cardoso et al 2000a, 2006, Cardoso & Vasconcelos 2004, Nascimento et al 2005, Oliveira Filho et al 2005.…”
Section: Introductionunclassified
“…No Brasil, esta bactéria foi identificada no muco vaginal de vacas leiteiras com histórico de repetição de estro no Estado de Alagoas (Oliveira Filho et al 2005). Os autores relataram que o isolamento do agente esteve associado à presença de lesões na mucosa vulvovaginal e concluíram que U. diversum deve ser considerado como agente responsável por queda na eficiência reprodutiva e retorno ao estro provavelmente em consequência de mortalidade embrionária.…”
Section: Introductionunclassified
“…In Austria, U. diversum was present in all studied farms with 35.5% of the animals testing positive for the organism, which was associated with vaginitis (Petit et al 2008). Previous studies reported a predominance of mild GVV in more than 50% of repeat breeding dairy cows with samples positive for U. diversum associated with this lesion grade (Oliveira Filho et al 2005). In beef heifers, there was a predominance of mild to severe GVV that was also associated with U. diversum (Gambarini et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In this study 100% of the uterine fragments (uterine horns and body) showed lesions scored as 4, with presence of four or more inflammatory alterations, besides the epithelium destruction and/or muscular necrosis (Figure 2, Panel a, b, d). The presence of mononuclear cells and glandular damage in the endometrium in repeat breeding cows was correlated with the presence of Ureaplasma diversum in the herd (Galindo et al 2004, Oliveira Filho et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…They are opportunists, which colonize the reproductive tract of females and males and are involved in the infertility of many species, including humans and bovines, different from the other members of this class due to the ability to hydrolyze urea in carbon dioxide and ammonia, which is one of the responsible factors of the cilliostatic activity of the ureaplasmas. Ureaplasma diversum is the only specie in bovines, causing outbreaks of granular vulvovaginitis syndrome (GVS) and cervicitis (Ahmadi et al 2006, Husted 2003, followed by abortion and reduction of the reproductive efficiency of the herd (Oliveira Filho et al 2005).…”
Section: Introductionmentioning
confidence: 99%